2002
DOI: 10.1001/archopht.120.3.348
|View full text |Cite
|
Sign up to set email alerts
|

Partial Antagonism of Endothelin 1–Induced Vasoconstriction in the Human Choroid by Topical Unoprostone Isopropyl

Abstract: Background: There is increasing evidence that reduced ocular blood flow plays a role in the pathogenesis of glaucoma. In patients with normal-tension glaucoma, ocular blood flow abnormalities may be associated with dysfunction of the endothelin 1 (ET-1) regulation system. Objective: To test the hypothesis that unoprostone, a topical docosanoid, may affect ET-1-induced vasoconstriction in the human choroid. Methods: In a placebo-controlled, randomized, doublemasked, 2-way crossover design, ET-1 (2.5 ng/kg per m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…In this placebo-controlled study, it was shown that intravenous injection of ET-1 decreased choroidal blood flow. This effect was significantly blunted when topical unoprostone was coadministered (Polska et al, 2002).…”
Section: Improvement Of Ocular Blood Flow By Prostaglandin F Analoguesmentioning
confidence: 96%
See 1 more Smart Citation
“…In this placebo-controlled study, it was shown that intravenous injection of ET-1 decreased choroidal blood flow. This effect was significantly blunted when topical unoprostone was coadministered (Polska et al, 2002).…”
Section: Improvement Of Ocular Blood Flow By Prostaglandin F Analoguesmentioning
confidence: 96%
“…In this placebo-controlled study, it was shown that intravenous injection of ET-1 decreased choroidal blood flow. This effect was significantly blunted when topical unoprostone was coadministered (Polska et al, 2002).Different animal studies revealed a direct, IOPindependent effect of PG analogues on blood flow. In rabbits ET-1 decreased optic nerve head blood flow.…”
mentioning
confidence: 96%
“…Further, a possible antagonistic effect between endothelin 1 and unoprostone in the choroidal vasculature has been reported [86]. Travoprost.…”
Section: Prostaglandismentioning
confidence: 96%
“…Compared to latanoprost, unoprostone seems to be less effective in extent and duration of IOP reduction [69]. Recent evidence suggests that topical applied unoprostone increases optic nerve head, choroidal and retinal blood flow and an antagonistic effect of endothelin-1 induced vasoconstriction in the human choroid has been observed [70,71]. No darkening of the iris colour is induced.…”
Section: Prostaglandinsmentioning
confidence: 99%